2023
DOI: 10.3102/01623737231155155
|View full text |Cite
|
Sign up to set email alerts
|

The Plight of Persistently Disciplined Students: Examining Frequent Flyers and the Conversion of Office Discipline Referrals Into Suspensions

Abstract: Racial inequality in exclusionary discipline is a salient educational equity issue. The implications of educators’ discretion in administering discipline and the complexity of repeated office discipline referrals (ODRs) and suspensions are reflected in school discipline policy debates nationwide. This brief uses New York City to learn more about persistently disciplined students. Black students are more likely to be persistently referred than other students. The disparities in the students who are persistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(62 reference statements)
0
8
1
Order By: Relevance
“…Consistent with the current study, Smolkowski and colleagues (2016) found that Black students were more likely to receive ODRs for subjective behaviors (e.g., defiance, disrespect) and male students were much more likely to receive ODRs. While prior work suggests Black and Latino/a/e students tend to receive harsher disciplinary sentences than White students (Liu et al, 2022a; Welsh & Rodriguez, 2023), our work finds different disparities in how teachers talk about students of color. The fact that teachers writing about Latino/a/e students used fewer negative emotions in ODRs relative to White students may reflect a psychological difference in how teachers attend to students of different ethnicities.…”
Section: Discussioncontrasting
confidence: 74%
“…Consistent with the current study, Smolkowski and colleagues (2016) found that Black students were more likely to receive ODRs for subjective behaviors (e.g., defiance, disrespect) and male students were much more likely to receive ODRs. While prior work suggests Black and Latino/a/e students tend to receive harsher disciplinary sentences than White students (Liu et al, 2022a; Welsh & Rodriguez, 2023), our work finds different disparities in how teachers talk about students of color. The fact that teachers writing about Latino/a/e students used fewer negative emotions in ODRs relative to White students may reflect a psychological difference in how teachers attend to students of different ethnicities.…”
Section: Discussioncontrasting
confidence: 74%
“…Compared to ODRs, suspensions are more closely aligned with the disciplinary decisions made by school leaders in accordance with the school district's disciplinary code (Welsh, 2022b(Welsh, , 2023aWelsh & Rodriguez, 2023). In practice, the disciplinary code in NYC permits school administrators to choose from a variety of disciplinary options for a particular level of infraction-there may be alternatives to exclusionary discipline for school leaders to choose from, such as restorative practices, especially for less severe infractions that are nonviolent and nonharmful.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike prior research that has typically examined how suspensions and expulsions affect families (Gibson & Haight, 2013; Gibson et al, 2014; Haight et al, 2014; Wahman et al, 2022), this study examines the role of the school-family relationship in predicting discipline disparities. Additionally, the study focus on both ODRs and suspensions to get a better understanding of how school-family relationships influence a complex disciplinary process in schools (Liu et al, 2022; Welsh, 2023a; Welsh & Rodriguez, 2023). Indeed, “simultaneously examining ODRs and suspensions as well as the relationship between these two interrelated disciplinary outcomes provides insights on whether teacher discretion or school administrator discretion or both is fueling racial inequities in exclusionary discipline” (Welsh & Rodriguez, 2023).…”
Section: School-family Relationships and School Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…School environments then become places where White bodies are easily forgiven or empathized with, whereas Black bodies are punished despite the availability of flexibility and leniency extended to White students. A growing number of recent studies have provided empirical evidence of Black students’ experiences with differential treatment from teachers and school leaders who punish Black students more often, more harshly, and for longer periods of time than White students for similar behaviors (both subjective and nonsubjective disciplinary infractions) or the same incident (Barrett et al, 2021; Carter et al, 2017; Lewis & Diamond, 2015; Liu et al, 2022; Rodriguez & Welsh, 2022; Shi & Zhu, 2022; Skiba et al, 2002; Welsh, 2022; Welsh & Rodriguez, 2023). For instance, Barrett et al (2021) found that Black students receive longer suspensions than their White counterparts also involved in the same, interracial fight (i.e., students of different racial backgrounds in the same fight or involved in the same incident type).…”
Section: Antiblackness In School Disciplinementioning
confidence: 99%